City Educational Environment in Terms of Anthropopractices of Care. The Idea of a Configurator - S. A. Smirnov (Moscow Polytechnic University, 2020)
The article continues the author's series of publications aimed at building an educational cultural configurator which ties three themes into a single knot - the sphere of education, the City and the Person. A cross-cutting cultural "glue" of this bundle is the experience of anthropological practitioners of human care for themselves, through which, doing which, a person is becoming his true self. The paper proposes to consider the experience of compiling such a repertoire of anthropopractices of care, which sets the completeness of the care experience. The completeness of the repertoire of anthropological practitioners can be represented only in one cultural image - the image of the City, in which it is possible to build a real educational navigation of a person. Based on the experience of other researchers, the author proposes a configurator that combines the repertoire of anthropopractices of care, the fullness of cultural forms that make up the city space, and the universe of a person's personality, formed through the experience of the practices of caring in a person. Thus, a cultural invariant is proposed, which can be laid at the basis of various educational programs for human development, overcoming various kinds of reductions that that are inherent in modern educational practice.